HIGH PREVALENCE OF ANTIBIOTIC RESISTANCE IN SALMONELLA AND ESCHERICHIA COLI ISOLATED FROM PIG FARMS AND SLAUGHTERHOUSES IN NORTH VIETNAM - Thai, Truong Ha; Ngoc, Pham Thi; Lan, Nguyen Thi; Huong, Chu Thi Thanh (Journal of Agriculture and Technology Management, 2018)
This study presents the high prevalence  of antibiotic resistance of Salmonella and E. coli at the pig farms and related slaughterhouses in three provinces and two cities at the north Vietnam. Salmonella and E. coli were highly isolated from the sewages, anus feces, caecum, slaughterhouse’s floors, animal keeping floors, piggery floors, and carcass samples. The prevalence of Salmonella were 14.0% and 40.9%, and meanwhile E. coli were 68.2% and 67.2% of the collected samples at the pig farms and slaughterhouses, respectively. Among the 189 Salmonella isolates, 179 isolates were serotypeable belong to 10 serovars. Derby (21.7%) was the most common serovar, followed by Typhimurium (18.5%), Anatum (14.3%), Rissen (12.2%) and London (8.5%). The other serovars were Agona, Weltevreden, Meleagridis, Braenderup, and Chartres. Resistance to streptomycin (81.5% and 78.0%), tetracycline (78.3% and 89.0%), and ampicillin (55.6% and 64.0%) were most commonly observed in Salmonella and E. coli , respectively. Markedly lower resistance rates were observed in both of these bacteria for trimethoprim, nalidixic acid, ceftazidime, norfloxacin, nitrofurantoin, ciprofloxacin, and gentamicin. Interestingly, decreased susceptibility to quinolones group (ciprofloxacin, norfloxacin, and nalidixic acid) and third generation cephalosporins (ceftazidime) was commonly detected in the Salmonella and E. coli isolates. Moreover, resistance rates of the E. coli isolates to trimethoprime, norfloxacin, nalidixic acid, ciprofloxacin, and gentamicin were significantly higher than those in the Salmonella isolates (P<0.05).